The influence of a chronic L‐carnitine administration on the plasma metabolome of male Fischer 344 rats*. Issue 5 (10th February 2017) - Weinert, Christoph H.; Empl, Michael T.; Krüger, Ralf; Frommherz, Lara; Egert, Björn; Steinberg, Pablo; Kulling, Sabine E.
Abstract : This study investigates if a chronic oral supplementation of L‐carnitine causes metabolic changes in the plasma metabolite profile. Fischer 344 rats were supplemented with 0 to 0.5 g/L L‐carnitine per day for one year. Plasma samples were analyzed with three different analytical platforms. Concentrations of 29 out of 359 reproducibly quantified metabolites were significantly changed by L‐carnitine, but most of them only slightly. However, plasma TMAO increased up to tenfold. Abstract : Scope: L‐carnitine has been advertised as a fat‐lowering and performance‐enhancing supplement, although scientific evidence for its effectiveness is lacking. The uptake of about 1–2 g of L‐carnitine per day may result in the formation of metabolites like trimethylamine‐ N ‐oxide (TMAO), which in turn may be converted to potential carcinogens or promote the development of cardiovascular diseases. Methods and results: To assess whether an L‐carnitine supplementation changes overall metabolism or causes the formation of previously unknown metabolites, we analyzed plasma samples from Fischer 344 rats originating from a previous study2 using a multi‐platform metabolomics approach comprising LC‐MS/MS and GC×GC‐MS methods. Despite an intake of up to 352 mg L‐carnitine/kg body weight/day for 1 year, plasma concentrations of only 29 out of 359 metabolites were significantly influenced, the induced concentration changes being often comparatively small. Nevertheless, a clear dose‐response relationship and a substantial concentration increase were observed for TMAO, i.e. a tenfold higher TMAO level was measured in the high‐dose group when compared to the control (2.5 versus 25.0 μM). Conclusion: Although L‐carnitine supplementation did not cause large changes in the plasma metabolome, a higher risk for cardiovascular disease due to chronically elevated TMAO plasma concentrations cannot be excluded.